Isolasi dan Penentuan Struktur Molekul Alkaloid dari Strychnos ligustrida Bl. - Judhi Rachmat; Titik K. Prana; Partomuan Simanjuntak (Fakultas Farmasi Universitas Pancasila, 2004)
Four alkaloids, brucine, brucin N-oxide, colobrine N-oxide, and strychine N-oxide were isolated from the bark of Strychnos ligustrida Bl. (Loganiaceae). Their structures were determined by spectroscopic data analysis, in particular by the Nuclear Magnet Resonance ('H and 13C NMR) and 2D NMR ('H-'HCOSY, 13C-'H COSY) and mass spectroscopy (MS).